(untitled) (Semiárida, 2026)
The presence of Gaillardia cabrerae Covas (Asteraceae) is documented for the first time in the province of Río Negro, in the North of Argentine Patagonia. This finding is significant considering that, so far, this species was considered endemic to La Pampa, with few records in scattered populations throughout the province. After discoveries of the species’ presence in ravines along the Colorado River in La Pampa territory, new surveys have located population nucleus within the Río Negro jurisdiction. These sites correspond to rocky outcrops of low high located at the height of Loma de Tomassen, very close to those already recognized for the Choique Mahuida Mountains on La Pampa side. Given that for a long time G. cabrerae was considered an exclusively endemic species of Lihué Calel National Park, these new findings in unprotected areas imply considerations regarding its conservation. In particular, the construction of a dam at the site could lead to the loss of the only known population in Río Negro due to potential flooding.